1995
DOI: 10.1002/jcp.1041630202
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory action of prolactin on the in vitro growth of CD34+ve human hemopoietic progenitor cells

Abstract: The pituitary hormone prolactin (Prl) is known to act as a local regulator of immune cell function, and Prl-binding receptors (Prl-R) have been described to share distinctive features with the members of the newly described cytokine/hemopoietin receptor superfamily. Here we show that the hormone can functionally interact with lineage-specific hemopoietic factors. When highly purified progenitor cells (CD34+ve) were seeded in semisolid methylcellulose cultures in the presence of interleukin (IL)-3, granulocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 50 publications
2
43
1
Order By: Relevance
“…Treatment with PRL in serum-free medium independently or synergistically with IL-2 enhanced the natural cytotoxicity of human NK and lymphokine-activated killer cells to tumor targets (7). PRL was reported to improve stem cell differentiation in a semisolid colony assay system (5). We also observed that PRL administration increased the antigen-specific proliferation of lymph node T cells in both normal and dwarf mice (20).…”
mentioning
confidence: 90%
“…Treatment with PRL in serum-free medium independently or synergistically with IL-2 enhanced the natural cytotoxicity of human NK and lymphokine-activated killer cells to tumor targets (7). PRL was reported to improve stem cell differentiation in a semisolid colony assay system (5). We also observed that PRL administration increased the antigen-specific proliferation of lymph node T cells in both normal and dwarf mice (20).…”
mentioning
confidence: 90%
“…PRL and GH play a role in stimulating the hematopoietic system (Bellone et al, 1995;Richards and Murphy, 2000). PRL enhances granulocyte/macrophagecolony stimulating factor (GM-CSF)-mediated maturation of CD34ϩ human hematopoietic progenitor cells into erythroid precursors in culture (Bellone et al, 1995).…”
Section: Prolactin and Hematopoiesismentioning
confidence: 99%
“…PRL enhances granulocyte/macrophagecolony stimulating factor (GM-CSF)-mediated maturation of CD34ϩ human hematopoietic progenitor cells into erythroid precursors in culture (Bellone et al, 1995). Pharmacologic levels of PRL increase the hematopoietic progenitors of the myeloid (colony-forming unit-granulocyte macrophage, or CFU-GM) and erythroid (blast-forming unit-erythocyte, or BFU-E) lineages in the bone marrow and spleen, during myelosuppression following treatment for HIV infection or bone marrow transplantation (Richards and Murphy, 2000).…”
Section: Prolactin and Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…They thus become active T-cell stimulators. Because PRL has been shown by our group to interact with GM-CSF, 16,17 we have here addressed its possible involvement, alone or in combination with GM-CSF, in the process of DC maturation and antigen presentation. Sigma-Aldrich s.r.l (Gallarate, Milan, Italy).…”
Section: Introductionmentioning
confidence: 99%